TUJUAN DAN MANFAAT PENGEMBANGAN RANAH AFEKTIF: TUJUAN DAN MANFAAT PENGEMBANGAN RANAH AFEKTIF - Nelmi hafizah Mokoginta; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
Development of emotional learning techniques, such as value-related techniques that are challenging to quantify in light of the awareness that each person has. Any circumstance that involves conflict or challenges is typically met with attitudes that are a reflection of its value. The process of modeling is frequently used in the affective formation phase of the learning strategy. In contrast, the emotional learning strategy model uses model konsiderasi, a model of cognitive growth, value clarification methods, a model of cognitive morality, and a non-directive model. The traits in the emotional learning field that are concerned with attitudes, interests, values, morals, and self-concept. Along with components of cognitive and psychomotor skill development, it's equally crucial to foster student attitudes in order for kids to behave